The Effect of Career Planning on Employee Performance Through Work Motivation as a Mediator for Generation Z Employees in Yogyakarta - Marsaoli, Rahmatika Chaerani; Widyatmoko, Widi Fajar (CV. Rayyan Dwi Bharata, 2026)
Employee performance is a key factor for organizational success in the post-pandemic era, which is characterized by global economic challenges and high rates of resignation, especially among Generation Z. like lack of planning career, motivation Work low often time hinder Employee productivity. This study aims to analyze the effect of career planning on employee performance through work motivation as an intervening variable, on Generation Z employees in Yogyakarta. Using a quantitative approach with Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) through SmartPLS. 4, study This involving 134 respondents Which chosen through purposive sampling . Data were collected using a Likert- scale questionnaire. Results study show: (1) planning career has a positive and significant effect on employee performance (T=6.178, P=0.000); (2) planning career increase motivation Work (T=14,572, P=0.000); (3) work motivation mediates the relationship between career planning and employee performance (T=5.176, P=0.000); (4) work motivation has a positive effect on employee performance (T=5.512, P=0.000); (5). The model explains 52.1% of the variation in work motivation and 83.4% of the variation in employee performance. These findings emphasize the importance of structured career planning to improve the performance of Generation employees.